Improving Madrasah Ibtidaiyah Students’ Learning Motivation and Cognitive Outcomes in the Fiqh Subject Using the Iconnu Model - Maskur Maskur; Ibnu Hadjar; Ridwan Ridwan; Nurkaenah Nurkaenah (Universitas Islam Negeri (UIN) Salatiga, 2025)
Objectives: This study investigates the implementation of Iconnu learning model to increase student interest and improve learning outcomes. Method: This one-group pretest-posttest quasi-experimental study was conducted in the 4th grade class at Madrasah Ibtidaiyah Negeri in Semarang City. The sampling technique used was purposive sampling. Data were collected through interviews, questionnaires, documentation, and observation. Data were analyzed using descriptive statistical formulas. Results: This study shows thatthe Iconnu learning model was validated by experts with an average score of 3.90, increased student learning motivation by 46.7%, and iimproved cognitive learning outcomes by 46.4%. This study also found the syntax of the Iconnu learning model, which consists of four stages, namely; 1) Preliminary Learning Stage; 2) Collaborative Learning Stage; 3) Interactive Learning Stage; 4) Questioning Stage.Contribution of theory: The results of this research have provided theoretical contributions in the form of; 1) simplifying the syntax of the Connac and Codac-based constructivist learning theory from seven steps to four; 2) Strengthening the theory of Islamic education that highlights the obligation to seek knowledge (fardu 'ain) and the use of reason in learning.Limitations & Recommendations: This research is limited to one public school and one subject. Therefore, the researchers suggest further research with a wider range of location and for other subjects.